Investment Of Islamic Aqidah In Children Since - Darni Kurnianingsih (Proceeding International Seminar of Islamic Studies, 2019)
The majority of causes of damage to children are due to parents ignoring them, and not teaching various obligations and religious teachings. Many of us also see around us parents or educators frighten children with superstition and other things that are prohibited by Sharia which can be a cause damage to the aqeedah which is the basis of Islam. Early childhood is the most important time for planting the foundation of true faith and teaching the Koran because at that time the nature of the child is still clean. When the creed has been firmly embedded in the heart, the child will become a figure of a faithful person with a strong personality, both in his attitude and deeds because he always feels under God's supervision, and minimizes children from doing bad deeds, such as saying dirty, deceiving, and others can make a useful generation for family, community and country.